Treatment with antibodies against primary group A streptococcal peritonitis: A case report and a review of the literature. Issue 52 (December 2017) - Iitaka, Daisuke; Ochi, Fumiaki; Nakashima, Susumu; Fujiyama, Jyunshin; Masuyama, Mamoru
Abstract: Rationale: Several reports describe severe group A streptococcal (GAS) infections causing septic shock, soft-tissue necrosis, and multiple organ failure known as streptococcal toxic shock syndrome (STSS). However, primary peritonitis with GAS is rare and most of them were undertaken surgical procedure. Patient concerns: We herein reported the case of 26-year-old healthy woman with sudden severe abdominal pain and hypotension. Computed tomography (CT) showed that large amount of free fluid in the peritoneal cavity consist with peritonitis, and no free air. Diagnoses: Primary peritonitis with GAS. Interventions: Proper antibiotic therapy according to blood culture results. Outcomes: After antibiotic therapy, the patient recovered well without complications. Lessons: An appropriate diagnostic approach and prompt antibiotic therapy is essential in GAS primary peritonitis.